Adsorption of 1,2-Dichloropropane from Aqueous Solution onto Activated Carbon - Robert Pelech; Eugeniusz Milchert (Adsorption Science & Technology)
An analysis of the adsorption of 1,2-dichloropropane (DCP) from aqueous solution onto activated carbon was presented. The adsorption equilibrium was described by the Freundlich and Dubinin-Astakhov equations. The dependence of the adsorption isosteric heat on the fractional equilibrium adsorption was determined and described by Do's model. A pseudo-second-order rate equation describing the adsorption kinetics of DCP from aqueous solution onto the activated carbon at different initial concentrations, adsorbent dose, temperature, particle diameter and the rate of stirring was established and the rate constant calculated. The mass-transfer coefficient was described by the Arrhenius equation. The adsorption activation energy of DCP onto activated carbon was 22.248 kJ/mol.